Seismic response of selective pallet racks along down-aisle direction, subjected to far-field and near-field ground motions - Ipe, Bennet A.; Sajith, A.S. (Journal of Structural Engineering, 2024)
This paper presents the findings of the incremental dynamic analysis of a two-bay, four-shelf selective pallet rack alongthe down-aisle direction under a set of far-field and near-field ground motions. The numerical study employs a pivothysteresis model to simulate the hysteresis behaviour of the connections between the beam and upright. The approachproposed by Firouzianhaji is implemented to derive the backbone curve of the hysteresis model from the results of the monotonic cantilever tests. The study examines two cases in which the total mass of the pallets is either 8000 kg or 4000 kg, with the total mass distributed uniformly on all four beams of the shelves for either case. The results indicate that racks supporting a heavier pallet mass of 8000 kg mostly have lower frame capacities than racks supporting 4000 kg of pallet mass. The structural behaviour of the racks shows characteristics similar to a soft story, with larger values of connection rotations and shelf-level displacement observed at the first shelf level. The frame capacities of specific pallet racks are notably reduced when subjected to near-field ground motions with a higher PGV/PGA ratio (exceeding 0.2), highlighting the potential for collapse in these earthquakes. Fling-step type artificial pulses generate larger responses compared to forward-directivity type pulses, for the same acceleration amplitude, with the response parameters indicating higher values for fling-step type pulses at a period ratio of 1.2 and for forward-directivity type pulses at a ratio of 1.0.